3(2x-6)+6(x-2)=3(3-5x)+5x-7

Simple and best practice solution for 3(2x-6)+6(x-2)=3(3-5x)+5x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-6)+6(x-2)=3(3-5x)+5x-7 equation:


3(2x-6)+6(x-2)=3(3-5x)+5x-7

We simplify the equation to the form, which is simple to understand
3(2x-6)+6(x-2)=3(3-5x)+5x-7

Reorder the terms in parentheses
+(+6x-18)+6*(x-2)=3*(3-5x)+5x-7

Remove unnecessary parentheses
+6x-18+6+*(+x-2+)=+3+*(+3-5x+)+5x-7

Reorder the terms in parentheses
+6x-18+(+6x-12)=3*(3-5x)+5x-7

Remove unnecessary parentheses
+6x-18+6x-12=+3+*(+3-5x+)+5x-7

Reorder the terms in parentheses
+6x-18+6x-12=+(+9-15x)+5x-7

Remove unnecessary parentheses
+6x-18+6x-12=+9-15x+5x-7

We move all terms containing x to the left and all other terms to the right.
+6x+6x+15x-5x=+9-7+18+12

We simplify left and right side of the equation.
+22x=+32

We divide both sides of the equation by 22 to get x.
x=1.45454545455

See similar equations:

| 4(x-2)-3(x-1)=2(x+6) | | (3x-4)(x^2-6x+6)= | | (x+5)(x+5)=25 | | (11+i)+(3-15i)= | | (x^2+15)(x+30)=3000000 | | 6x(x-1)=7-25x | | (x^2+15)(x+30)=300 | | x^2=5(x+280) | | (-4+3i)-(-1+6i)= | | (2x^3+12)(x^2-15)=117 | | (2x^3+12)(x^2-15)=333 | | -4c(3+5)=32 | | (2x^3+12)(x^2-15)=2103 | | (2x^3+12)(x^2-15)=10 | | 9x^2=6x+3 | | (2x^3+12)(x^2-15)=0 | | (2x+4)-3x=-3(x+7) | | (3x+7y^5-5)(13y-7x^2)=3.14 | | t+(-2)=66 | | 4m=m+9 | | 33+(-7)=29+m | | -33+(-7)=29 | | 14y-4=3y | | 2x^2+(3x-5)=37 | | (3x^4+4x^3-5)-(8x^2-5x+8)= | | x-7y-14=0 | | x+2y=-13 | | 176=H+(219) | | (2x^2)=(3x^2-64) | | y=6x+b | | b=y-6x | | 2x+y=-14 |

Equations solver categories